2007
DOI: 10.1007/s10751-008-9655-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of hyperfine interactions in carbonaceous chondrite Isheyevo (CH/CB) using Mössbauer spectroscopy with high velocity resolution

Abstract: The unique meteorite bencubbinite Isheyevo CH/CB which was recently found in Bashkortostan, Russia was studied using Mössbauer spectroscopy with high velocity resolution. Mössbauer hyperfine parameters of metal in Isheyevo CH/CB external and internal regions demonstrated the presence of three phases such as martensite α 2 -Fe(Ni,Co), kamacite α-Fe(Ni,Co) and disordered taenite γ-Fe(Ni,Co).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…This meteorite contains from 50 to 70 vol% of Fe-Ni-Co alloy and has weathering grade W1. This meteorite was studied by Mössbauer spectroscopy with a high velocity resolution in [43]. The authors analyzed external and internal parts of meteorite fragment, which spectra are shown in Figure 4.…”
Section: Carbonaceous Chondritesmentioning
confidence: 99%
See 1 more Smart Citation
“…This meteorite contains from 50 to 70 vol% of Fe-Ni-Co alloy and has weathering grade W1. This meteorite was studied by Mössbauer spectroscopy with a high velocity resolution in [43]. The authors analyzed external and internal parts of meteorite fragment, which spectra are shown in Figure 4.…”
Section: Carbonaceous Chondritesmentioning
confidence: 99%
“…Figure43. Classifications of H, L, and LL ordinary chondrites using the relative areas obtained from the Mössbauer spectra: the relative area of pyroxene vs. the relative area of olivine (a) and the relative area of metallic phase vs. the relative area of silicate phases (b).…”
mentioning
confidence: 99%
“…Isheyevo contains from 50 to 70 vol.% of Fe-Ni-Co alloy, its weathering grade is W1. The external and internal parts of one Isheyevo fragment were studied by Mössbauer spectroscopy with a high velocity resolution at room temperature in [33]. The measured spectra are shown in Figure 14a,b.…”
Section: Carbonaceous Chondritesmentioning
confidence: 99%
“…The measured spectra are shown in Figure 14a,b. These spectra were refitted with a larger number of components, than that used earlier in [33]. Equal Γ values for magnetic sextets which were varied during the new fit were also used.…”
Section: Carbonaceous Chondritesmentioning
confidence: 99%
“…Further development of Mössbauer spectrometers to increase velocity resolution up to 4096 channels (a high velocity resolution) in the spectrum leads to decrease in the instrumental (systematic) error on the velocity scale and better fit of complicated Mössbauer spectra due to increase in the number of spectral points (see technical advances in [4][5][6]). Study of meteorites and its iron-bearing phases using Mössbauer spectroscopy with a high velocity resolution demonstrated new possibilities in revealing data which could not be obtained from Mössbauer spectra measured with a low velocity resolution [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Therefore, in this work we consider further results of the study of some ironbearing minerals from some meteorites obtained using Mössbauer spectroscopy with a high velocity resolution.…”
Section: Introductionmentioning
confidence: 99%